A rare case of schwannoma of the small intestine discovered during intussusception - Sachiyo Onishi; Takashi Ibuka; Yukari Uno; Kentaro Kojima; Jun Takada; Masaya Kubota; Masahito Shimizu (JGH Open)
Abstract A woman in her 60s with anemia was diagnosed with a small intestinal intussusception on computed tomography. She underwent a double‐balloon endoscopy, which revealed submucosal tumor in the ileum. Suspected to be the cause of anemia and intussusception, surgical intervention was carried out, revealing it to be a schwannoma. Schwannomas of the small intestine are very rare, and because exophytic growths are common, intussusception due to luminal side development is even rarer.